We've Come a Long Way Baby. Issue 3 (1st March 2017) - Cooper, Robert G.
Abstract : See virtual issue: Collecting Robert G. Cooper's Articles as Author or Co‐Author from the Journal of Product Innovation Management, 1984–2016